2021
DOI: 10.1111/1755-0998.13426
|View full text |Cite
|
Sign up to set email alerts
|

Beyond taxonomy: Validating functional inference approaches in the context of fish‐farm impact assessments

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 91 publications
0
9
0
Order By: Relevance
“…In the deep sea, eDNA analysis has focused on the sediments to survey the benthic communities (e.g., Guardiola et al, 2016;Sinniger et al, 2016;Laroche et al, 2021). On the other hand, a few surveys of aquatic communities in the deep sea have been conducted (Fraija-Fernańdez et al, 2020;McClenaghan et al, 2020;Merten et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In the deep sea, eDNA analysis has focused on the sediments to survey the benthic communities (e.g., Guardiola et al, 2016;Sinniger et al, 2016;Laroche et al, 2021). On the other hand, a few surveys of aquatic communities in the deep sea have been conducted (Fraija-Fernańdez et al, 2020;McClenaghan et al, 2020;Merten et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Within a microbial community, diverse and multiple species can perform similar catabolic functions that affect the microbial community structure over time or in response to stimuli. To evaluate the functional capacity of the soil microbiome in sandy soil and rhizosphere sandy soil that received different treatments, Tax4Fun2 was used to predict functional features based on the 16S rRNA gene sequencing data. Our previous study reported desulfonation and defluorination enzymes involved in 6:2 FTSA biodegradation by RHA1 . So, the analysis was focused on these known desulfonation and defluorination enzymes.…”
Section: Resultsmentioning
confidence: 99%
“…These tools use hidden-state prediction (HSP) algorithms, which allow the estimation of metabolic functions based on representative genomic content from a well-described bacterial community. A key problem in using such databases is the relatively low correlation between the relative abundance of their specific functions [ 106 ] and the high population variability, limiting these tools in applications with defined cohorts.…”
Section: Focus On Bacterial Communitiesmentioning
confidence: 99%